A survey of advancements in nucleic acid-based logic gates and computing for applications in biotechnology and biomedicine. Issue 18 (4th March 2015) - Wu, Cuichen; Wan, Shuo; Hou, Weijia; Zhang, Liqin; Xu, Jiehua; Cui, Cheng; Wang, Yanyue; Hu, Jun; Tan, Weihong
<x xml:space="preserve">Abstract</x> Nucleic acid based logic systems have been rationally designed and functionalized to better serve bioanalytical and biomedical applications.